Respuesta :

Answer:

B

Step-by-step explanation:

Given

B = [tex]\frac{RT-4}{6}[/tex]

Multiply both sides by 6 to eliminate the fraction

RT - 4 = 6B ( add 4 to both sides )

RT = 6B + 4 ( divide both sides by R )

T = [tex]\frac{6B+4}{R}[/tex] → B

Answer:   [tex]\bold{b)\quad T=\dfrac{6B+4}{R}}[/tex]

Step-by-step explanation:

[tex]B=\dfrac{RT-4}{6}\\\\\\\text{Multiply both sides by 6:}\\6B=RT-4\\\\\text{Add 4 to both sides:}\\6B+4=RT\\\\\text{Divide both sides by R:}\\\large\boxed{\dfrac{6B+4}{R}=T}[/tex]